2016
DOI: 10.18632/oncotarget.9444
|View full text |Cite
|
Sign up to set email alerts
|

MiR-193a-5p/ERBB2 act as concurrent chemoradiation therapy response indicator of esophageal squamous cell carcinoma

Abstract: Concurrent chemoradiation therapy (CCRT) is the predominant treatment in esophageal cancer, however resistance to therapy and tumor recurrence are exceedingly common. Elevated ERBB2/Her2 may be at least partially responsible for both the high rates of recurrence and resistance to CCRT. This receptor tyrosine kinase is upregulated in 10–20% of esophageal squamous cell carcinoma (ESCC) tissues, and amplification of ERBB2 has been correlated with poor prognosis in esophageal cancer. Tissues from 131 ESCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…Over the past few years, miR-193a-5p has been found to be involved in multiple cancers, such as esophageal squamous cell carcinoma ( 14 ), bladder cancer ( 15 ), primary bone tumors ( 16 ), osteosarcoma ( 17 ), colorectal cancer ( 18 ) and endometrioid endometrial adenocarcinoma ( 19 ). Some noted pathways such as the PI3K/AKT signaling pathway, PTEN/AKT signaling pathway and mTOR signaling pathway have been implicated in the oncogenesis of different tumors and as therapeutic drug targets ( 20 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, miR-193a-5p has been found to be involved in multiple cancers, such as esophageal squamous cell carcinoma ( 14 ), bladder cancer ( 15 ), primary bone tumors ( 16 ), osteosarcoma ( 17 ), colorectal cancer ( 18 ) and endometrioid endometrial adenocarcinoma ( 19 ). Some noted pathways such as the PI3K/AKT signaling pathway, PTEN/AKT signaling pathway and mTOR signaling pathway have been implicated in the oncogenesis of different tumors and as therapeutic drug targets ( 20 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the 3'-untranslated region (UTR) of target mRNAs can be bound by specific miRNAs to play important roles in the regulation of radiation sensitivity of ESCC [18,19]. Wnt3 is a member of Wnt family, and is the key molecule of Wnt-β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For the included 96 studies, 52 were excluded because the frequency of them evaluating prognostic value of miRNA was equal to 1 3 , 4 , 16 , 18 23 , 26 , 30 , 31 , 39 46 , 48 , 53 , 54 , 56 , 60 , 61 , 64 74 , 77 86 , 92 96 . In addition, although one article reported OS results about miR-193a-5p, it was excluded because it had non-dichotomous miRNA expression value 105 . The mean NOS score of the included researches was 6.5 (4.0–8.0), indicating that the quality of them was adequate (Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%